2014
DOI: 10.1007/s10103-014-1668-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light-emitting diode (ʎ 627 nm and 945 nm ʎ) treatment on first intention healing: Immunohistochemical analysis

Abstract: Collagen I is not only responsible for maintaining the integrity of most tissues due to its mechanical properties, but also for its active participation in the functionality of tissues because of its interaction with cells present in the extracellular matrix. The synthesis of collagen begins with tissue injury and remains until the end of the healing process. The use of non-coherent light for healing processes is still understudied. This procedure stands out as a biostimulation method for tissue repair, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
0
22
0
3
Order By: Relevance
“…Chiarotto et al [20] found similar results using energy density of 4.48 J/cm2 in animals submitted to second degree burn, with a greater effectiveness of the laser 670 nm compared to 830 nm. Kerppers et al [25] reported that small doses of laser fractions at different times are more effective than higher doses in a single application because it sustains mitochondrial activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiarotto et al [20] found similar results using energy density of 4.48 J/cm2 in animals submitted to second degree burn, with a greater effectiveness of the laser 670 nm compared to 830 nm. Kerppers et al [25] reported that small doses of laser fractions at different times are more effective than higher doses in a single application because it sustains mitochondrial activity.…”
Section: Discussionmentioning
confidence: 99%
“…For the application of the PBM we used the HTM Compact ® Laser (Amparo, SP, Brazil, License: 80212480005) with a frequency of 60 Hz, power supply, and a maximum current of 54 mA. Table 1 presents the PBM parameters used with the same energy density standardized for the three groups (4 J/cm²) [24][25][26][27]. The application was given point by point [28], with the probe in perpendicular contact to the edge of the wound (0.5 cm), totaling 12 points ( Figure 1).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Muitos pacientes com disfagia apresentam odinofagia, problemas gástricos, doenças orais que dificultam o processo terapêutico (candidíase, herpes, gengivites, entre outros), edema, alterações de tônus e mobilidade dos músculos responsáveis pelo preparo e impulsionamento do bolo alimentar 23,24 . O LBI poderia auxiliar o fonoaudiólogo nesses casos com o uso do LASER vermelho para analgesia, ação anti-inflamatória e antimicrobiana 4,10,17 . O LASER vermelho no modo ILIB, aplicado na artéria radial tem efeito sistêmico e pode ser aplicado sem riscos ao paciente que muitas vezes está debilitado.…”
Section: -Normas De Segurança Do Lbiunclassified
“…Promieniowanie emitowane przez diody LED, działając m.in. poprzez stymulację proliferacji i dojrzewania fibroblastów, wpływa na zwiększenie syntezy kolagenu, elastyny, glikoprotein i glikozoamin oraz regulację aktywności metaloproteinaz w tkankach [13][14][15]. Pod wpływem promieniowania czerwonego i podczerwonego dochodzi też do degranulacji mastocytów i uwalniania m.in.…”
Section: Diody Elektroluminescencyjne Ledunclassified
“…Terapia światłem małych mocy wpływa na wszystkie trzy fazy gojenia ran: fazę zapalną, w której komórki zapalne migrują do rany, fazę proliferacyjną z pobudzeniem fibroblastów i makrofagów oraz fazę dojrzewania, w której nastę-puje proces przebudowy zagojonej już rany, aby stała się bardziej wytrzymała. Pod wpływem właściwie dobranego promieniowania świetlnego następuje zwiększenie produkcji oraz aktywacji fibroblastów i makrofagów, pobudzenie leukocytów i przyspieszenie tworzenia kolagenu oraz neowaskularyzacji [13,19]. Rany, w których przy stosowaniu klasycznych metod leczniczych proces gojenia nie przebiegał właściwie, ulegały zabliźnieniu po zastosowaniu naświetlania diodami LED emitującymi promieniowanie z zakresu widzialnego i bliskiej podczerwieni.…”
Section: Diody Elektroluminescencyjne Ledunclassified